Transmission rate factors among tuberculosis patients in West Kalimantan, Indonesia - Nita Arisanti Yulanda; Kharisma Aji Martadi; Titan Ligita; Ikbal Fradianto; Andikawati Fitriasari (PAGEPress Publications, 2023)
Tuberculosis is a critical issue in a community, and the rising number of cases can be attributed the development and evolution of the bacteria responsible. As part of independent nursing actions, educational intervention is a solution to improve prevention and treatment success at the family and community levels. This study aimed to determine the factors for Tuberculosis transmission. This research was a correlation study with a cross-sectional design, involving a sample of 100 participants selected through purposive sampling. Independent variables for the present study include age, gender, occupation, diabetes record, body mass index (BMI), and level of knowledge. Meanwhile, the dependent variable in this study is the risk of transmission. This observation used a questionnaire with chi-square and logistic regression analysis. The result showed that families with a thin body mass index had a lower likelihood of carrying out infectious behavior (p=0.000). Most respondents have a high level of knowledge and a low potential for infectious behavior. In fact, a good education system, it will allow someone to be independently trained to change behaviors and attitudes for the better.